2019
DOI: 10.1111/tbed.13219
|View full text |Cite
|
Sign up to set email alerts
|

Molecular characteristics and pathogenic assessment of porcine epidemic diarrhoea virus isolates from the 2018 endemic outbreaks on Jeju Island, South Korea

Abstract: Since the 2013-2014 incursion of the virulent G2b porcine epidemic diarrhoea virus (PEDV) pandemic strains in South Korea, frequent moderate-scale regional outbreaks have recurred. In particular, areas of Jeju Island with extensive swine production have faced repeated epidemics since the re-emergence in 2014. The current study reports the complete genome sequences and molecular characterization of the representative PEDV strains responsible for the 2018 endemic outbreaks on Jeju Island. All isolates were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(50 citation statements)
references
References 30 publications
0
50
0
Order By: Relevance
“…The suspensions were vortexed and centrifuged for 10 min at 4,500 × g (Hanil Centrifuge FLETA5, Incheon, South Korea). The clarified supernatants were initially subjected to RT-PCR analysis using a LiliF PED RT-PCR Kit (iNtRON Biotechnology, Seongnam, South Korea) according to the manufacturer's instructions and to quantitative real-time RT-PCR as described previously [9,10]. To determine if any other diarrhea-causing pathogens, besides PEDV, were present in clinical samples, we performed virus-specific RT-PCR analyses for transmissible gastroenteritis virus, porcine deltacoronavirus, and porcine rotaviruses.…”
Section: Clinical Sample Collectionmentioning
confidence: 99%
“…The suspensions were vortexed and centrifuged for 10 min at 4,500 × g (Hanil Centrifuge FLETA5, Incheon, South Korea). The clarified supernatants were initially subjected to RT-PCR analysis using a LiliF PED RT-PCR Kit (iNtRON Biotechnology, Seongnam, South Korea) according to the manufacturer's instructions and to quantitative real-time RT-PCR as described previously [9,10]. To determine if any other diarrhea-causing pathogens, besides PEDV, were present in clinical samples, we performed virus-specific RT-PCR analyses for transmissible gastroenteritis virus, porcine deltacoronavirus, and porcine rotaviruses.…”
Section: Clinical Sample Collectionmentioning
confidence: 99%
“…Notably, vaccination failure and high death rate as observed in the 2010 Chinese outbreak, with the reemergence of a more virulent PEDV [4], resulted in huge economic losses for the pig industry. Subsequently, PED rapidly spread to more than 30 states of the United States, causing its first outbreak in 2013 and significant damage to the US pork industry [5], following which further outbreaks were reported in Canada, Mexico, Korea, Germany, and Belgium [6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…S1) [6,8]. Genetic analysis indicated that the isolates were most closely related to the KNU-1815 strain (GenBank accession number MK032689), which was identified on farm A in early 2018 [12]. Both the KNU-1829 and -1830 viruses were found to contain a novel two-amino-acid (RG) deletion at positions 1,370 and 1,371 in the C-terminal region of the S protein, named S DEL, which is not present in the genome sequences of the other G1 and G2 strains available from the GenBank database ( Fig.…”
mentioning
confidence: 99%
“…In early October 2018, enteric and diarrheal diseases accompanied by low-to-moderate mortality rates (30-50%) in newborn piglets broke out almost simultaneously in two vaccinated farrow-to-finishing herds (farms A and B) in a Hallim-swine-dense region of Jeju Province. In particular, farm A experienced an acute PEDV infection in March 2018 [12]. Small-intestine specimens collected from diarrheic piglets at those farms were submitted to our laboratory for diagnosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation